Polar ice sheets are decisive contributors to uncertainty in climate tipping projections - Jonathan P. Rosser; Ricarda Winkelmann; Nico Wunderling (Communications Earth & Environment)
Abstract The Earth’s climate is a complex system including key components such as the Arctic Summer Sea Ice and the El Niño Southern Oscillation alongside climate tipping elements including polar ice sheets, the Atlantic Meridional Overturning Circulation, and the Amazon rainforest. Crossing thresholds of these elements can lead to a qualitatively different climate state, endangering human societies. The cryosphere elements are vulnerable at current levels of global warming (1.3  °C) while also having long response times and large uncertainties. We assess the impact of interacting Earth system components on tipping risks using an established conceptual network model of these components. Polar ice sheets (Greenland and West Antarctic ice sheets) are most decisive for tipping likelihoods and cascading effects within our model. At a global warming level of 1.5  °C, neglecting the polar ice sheets can alter the expected number of tipped elements by more than a factor of 2. This is concerning as overshooting 1.5  °C of global warming is becoming inevitable, while current state-of-the-art IPCC-type models do not (yet) include dynamic ice sheets. Our results suggest that polar ice sheets are critical to improving understanding of tipping risks and cascading effects. Therefore, improved observations and integrated model development are crucial.